Cultivating Energy Conscious Communities: The Path to Increased Efficiency - Lodewijk, Dewi Putriani Yogosara; Yandri, Erkata; Murdiyansah, Novan; Ariati, Ratna (Heca Sentra Analitika, 2024)
This research addresses the critical need for increased energy efficiency in communities, emphasizing the pivotal role of community involvement and awareness. With the growing concern for sustainable energy practices, empowering communities to contribute to energy efficiency initiatives is imperative. Thus, the research aims to investigate and understand the role of community empowerment in increasing energy efficiency through community role and awareness. The theory applied to the research is the theory of planned behavior. A descriptive quantitative approach is employed, utilizing a structured questionnaire based on the Likert scale. Then, after the questionnaires were collected, statistical data processing was carried out using the T-test, F-test, and validity and reliability tests. The questionnaire gauges participants' perceptions and behaviors about energy efficiency, enabling a comprehensive analysis of the community's role and awareness in promoting sustainable energy practices. Preliminary findings indicate a positive correlation between community empowerment, heightened awareness, and increased energy efficiency. The Likert scale responses provide valuable insights into the areas where communities excel and areas that require targeted interventions. The data also reveal notable patterns in community behaviors and perceptions of energy consumption and conservation. In conclusion, the research underscores the significance of community empowerment as a catalyst for enhancing energy efficiency. The findings suggest that fostering community awareness and active involvement can lead to tangible improvements in sustainable energy practices. This study contributes valuable insights for policymakers, community leaders, and energy advocates seeking effective strategies to address the global energy challenge through localized, community-driven initiatives.